Molecular Mechanisms Underlying Initiation and Activation of Autophagy - Zhixiao Wei; Xiao Hu; Yumeng Wu; Liming Zhou; Manhan Zhao; Qiong Lin (Biomolecules)
Autophagy is an important catabolic process to maintain cellular homeostasis and antagonize cellular stresses. The initiation and activation are two of the most important aspects of the autophagic process. This review focuses on mechanisms underlying autophagy initiation and activation and signaling pathways regulating the activation of autophagy found in recent years. These findings include autophagy initiation by liquid–liquid phase separation (LLPS), autophagy initiation in the endoplasmic reticulum (ER) and Golgi apparatus, and the signaling pathways mediated by the ULK1 complex, the mTOR complex, the AMPK complex, and the PI3KC3 complex. Through the review, we attempt to present current research progress in autophagy regulation and forward our understanding of the regulatory mechanisms and signaling pathways of autophagy initiation and activation.